Autoimmune encephalitis with coexistent LGI1 and GABABR1 antibodies: case report - Yi Xie (BMC, 2021)
Abstract Background Autoimmune encephalitis (AE) with multiple auto-antibodies is of great clinical significance because its complex clinical manifestations and atypical imaging increase the difficulty of diagnosis, differential diagnosis and treatment, which may aggravate the disease, increase the recurrence rate and mortality. The coexistence of anti-Leucinie-rich Glioma Inactivated 1 (LGI1) and anti-γ-aminobutyric acid-beta-receptor 1 (GABABR1) has not been published before. Case presentation We herein present the case of a 60-year-old man with slow response, behavioral changes, psychosis and sleep disorders. Laboratory test included serum hyponatremia, positive serum LGI1 and GABABR1 antibodies using transfected cell-based assays. Electroencephalogram exhibited moderate diffusion abnormality. The patient responded well to steroid impulse treatment and sodium supplement therapy, and did not recur during the follow-up. Conclusions Here we report the first AE characterized by positive LGI1 and GABABR1 antibodies, as well as summarizing AE with multiple auto-antibodies reported so far, hopefully to provide experience for clinical practice.